The driven readers amongst private higher education institution students: a case study - Osman, Syamsul Fozy; Sheikh Ahmad, Ismail (UPM Press, 2017)
The development of reading habits and the detrimental effects of its decline are intriguing issues to the proponents of reading. Findings or related research around the globe have resulted in discomforting outcomes, giving an indication that the habit is now facing a challenging period. However, an interesting phenomenon observable is that despite the unfavourable circumstances, there are individuals who are avid readers. This case study attempts to gather in-depth information on what motivates and influences private higher education institution students to become avid readers. Employing qualitative methods, information from two informants were analysed for essential clues on how motivation to read could be catalysed and sustained. Eleven major themes, namely, enjoyment, selfdevelopment, self-initiative, social support, reading friendly environment, unfriendly reading environment, reading motivates reading, curiosity motivates reading, author attraction, alliteracy awareness and spiritually motivated, surfaced from the analysis and they could prove invaluable towards the development of strategies to inculcate the reading habit.